2021
DOI: 10.1038/s41413-021-00139-z
|View full text |Cite
|
Sign up to set email alerts
|

Review of a new bone tumor therapy strategy based on bifunctional biomaterials

Abstract: Bone tumors, especially those in osteosarcoma, usually occur in adolescents. The standard clinical treatment includes chemotherapy, surgical therapy, and radiation therapy. Unfortunately, surgical resection often fails to completely remove the tumor, which is the main cause of postoperative recurrence and metastasis, resulting in a high mortality rate. Moreover, bone tumors often invade large areas of bone, which cannot repair itself, and causes a serious effect on the quality of life of patients. Thus, bone t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
113
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 161 publications
(114 citation statements)
references
References 177 publications
(198 reference statements)
1
113
0
Order By: Relevance
“…These results confirmed that temperature played a critical role in drug release, and the amount of drug released increased at higher temperatures, which was consistent with other carrier systems reported before [24]. Employing an appropriate vector is an important issue in developing a bone-targeting delivery system [40]. Based on the above information, the co-loaded NPs could be an extremely promising method of bone-targeted delivery.…”
Section: Discussionsupporting
confidence: 89%
“…These results confirmed that temperature played a critical role in drug release, and the amount of drug released increased at higher temperatures, which was consistent with other carrier systems reported before [24]. Employing an appropriate vector is an important issue in developing a bone-targeting delivery system [40]. Based on the above information, the co-loaded NPs could be an extremely promising method of bone-targeted delivery.…”
Section: Discussionsupporting
confidence: 89%
“…[ 2 ] Besides, the critical bone defects after surgery, drug‐resistance and side effects also attenuate the therapeutic effects and induce poor prognosis. [ 3 , 4 ] Notably, except for the elimination of tumor tissues, reconstruction of the critical bone defects afterward was also unsatisfactory currently and challenging. [ 3 , 5 , 6 ] Hence, more efficient and advanced platforms are instantly needed to be developed for achieving both effective OS elimination and enhanced bone regeneration.…”
Section: Introductionmentioning
confidence: 99%
“…Significant work has been dedicated to developing drug delivery system that can concurrently deliver PTX and Cur to the tumor site, which might provide improved therapeutic activity and safety. However, most reported carriers have limited loading capacity and there are also concerns regarding their possible toxicity and biodegradation (Hiremath et al, 2019;Li et al, 2019;Zhao et al, 2019;Shao et al, 2020;Xiong et al, 2020;Hu et al, 2021;Liao et al, 2021;Zhang et al, 2021). Carrierfree drug delivery systems are recently developed alternatives that do not rely on inert carriers and thus avoid potential toxicity.…”
Section: Introductionmentioning
confidence: 99%